Cyanobacteria of the Genus Prochlorothrix† - Pinevich, Alexander V.; Velichko, Nataliya V.; Ivanikova, Natalia V. (Frontiers in Microbiology, 2012)
Green cyanobacteria differ from the blue–green cyanobacteria by the possession of a chlorophyll-containing light-harvesting antenna. Three genera of the green cyanobacteria namely Acaryochloris, Prochlorococcus, and Prochloron are unicellular and inhabit marine environments. Prochlorococcus marinus attracts most attention due to its prominent role in marine primary productivity. The fourth genus Prochlorothrix is represented by the filamentous freshwater strains. Unlike the other green cyanobacteria, Prochlorothrix strains are remarkably rare: to date, living isolates have been limited to two European locations. Taking into account fluctuating blooms, morphological resemblance to Planktothrix and Pseudanabaena, and unsuccessful attempts to obtain enrichments of Prochlorothrix, the most successful strategy to search for this cyanobacterium involves PCR with environmental DNA and Prochlorothrix-specific primers. This approach has revealed a broader distribution of Prochlorothrix. Marker genes have been found in at least two additional locations. Despite of the growing evidence for naturally occurring Prochlorothrix, there are only a few cultured strains with one of them (PCC 9006) being claimed to be axenic. In multixenic cultures, Prochlorothrix is accompanied by heterotrophic bacteria indicating a consortium-type association. The genus Prochlorothrix includes two species: P. hollandica and P. scandica based on distinctions in genomic DNA, cell size, temperature optimum, and fatty acid composition of membrane lipids. In this short review the properties of cyanobacteria of the genus Prochlorothrix are described. In addition, the evolutionary scenario for green cyanobacteria is suggested taking into account their possible role in the origin of simple chloroplast.